2021
DOI: 10.3390/app11209508
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Machine and Deep Learning for Semiconductor Defect Classification in Scanning Electron Microscope Images

Abstract: Continued advances in machine learning (ML) and deep learning (DL) present new opportunities for use in a wide range of applications. One prominent application of these technologies is defect detection and classification in the manufacturing industry in order to minimise costs and ensure customer satisfaction. Specifically, this scoping review focuses on inspection operations in the semiconductor manufacturing industry where different ML and DL techniques and configurations have been used for defect detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…In the following article [21], authors used five machine learning models to classify minerals, including Logistic Regression, Linear Support Vector Machine, k-Nearest Neighbor, Random Forest, and Artificial Neuron Networks, and a deep learning CNN U-Net model, concluded that Random Forest outperformed with a F1 score of 0.92. In [22] authors classified the semiconductor defects in SEM images. It is evident that the prior research produced better outcomes than our own findings.…”
Section: Low Complexity Algorithm Resultsmentioning
confidence: 99%
“…In the following article [21], authors used five machine learning models to classify minerals, including Logistic Regression, Linear Support Vector Machine, k-Nearest Neighbor, Random Forest, and Artificial Neuron Networks, and a deep learning CNN U-Net model, concluded that Random Forest outperformed with a F1 score of 0.92. In [22] authors classified the semiconductor defects in SEM images. It is evident that the prior research produced better outcomes than our own findings.…”
Section: Low Complexity Algorithm Resultsmentioning
confidence: 99%
“…Ref. 5 reviewed nine ML-based semiconductor SEM defect detection studies published in and before 2020. They found that Convolutional neural networks (CNNs) Ref.…”
Section: Related Workmentioning
confidence: 99%
“…While these automated techniques have shown promise in detecting and analyzing defects, they still have some limitations in terms of robustness and performance when compared to the skill and expertise of a trained human operator. But in the recent years deep-learning enabled significant improvements [1].…”
Section: Introductionmentioning
confidence: 99%